Feasibility of a Regionwide Probability Survey for Coral Reef Fish in Puerto Rico and the U.S. Virgin Islands. Issue 1 (1st January 2016) - Bryan, David R.; Smith, Steven G.; Ault, Jerald S.; Feeley, Michael W.; Menza, Charles W.
Abstract: Fishery-independent surveys can provide accurate and precise data for stock assessments and spatial management to sustain fishery resources as a complementary or alternative source of information to fishery-dependent sampling. Four years of underwater visual survey data collected in several local areas in the U.S. Caribbean were used in conjunction with detailed bathymetric and habitat maps to develop a probability sampling design and investigate the feasibility of conducting a regionwide coral reef fish survey. Stratification by depth and habitat produced a more efficient survey design (i.e., one with increased precision at lower sample sizes) for estimating mean fish density than simple random sampling for eight principal exploited and nontarget species. Species with higher sample variance of density required larger sample sizes to improve survey precision. A somewhat counterintuitive finding was that controlling survey precision over a large spatial scale (i.e., region) required less sampling than controlling precision for multiple smaller areas within the larger survey frame. At regionwide spatial scales relevant for fisheries management, the projected sample sizes for achieving moderately high levels of survey precision were comparable to historical annual sampling efforts. However, controlling survey precision both inside and outside spatial management zones would likely require sample sizes about twice the level of the historical effort. Our findings stress the importance of clearly defining management objectives with respect to spatial scales and target species as a prerequisite for developing precise, cost-effective fishery-independent surveys. Received April 4, 2015; accepted August 4, 2015